Internal explosion load distribution and strain response of ellipsoidal end cover of explosion containment vessel. (March 2020) - Hu, Y H; Gu, W B; Liu, J Q; Han, Y M; Wang, Z
Abstract: As a kind of limitation device of explosive products and shock wave, explosion containment vessel is widely used in military and civil fields. Due to its own structural characteristics, Mach wave convergence and collision will occur near the pole of the end cover of the cylindrical explosion containment vessel, resulting in a great pressure jump and seriously affecting the strain response characteristics of the end cover. In this paper, by means of experiment and numerical simulation, the distribution of flow field inside the end cover was explored, and it was found that the initial load of the end cover pole included the first incident wave of internal explosion, convergent re-incident wave of central section and the Mach wave convergence wave. By analyzing the strain spectrum, it is found that the different frequencies are excited by loads at different locations, so that the energy distribution under each frequency of strain is different, resulting in differences of strain. These results can provide reference for the design of explosion containment vessel.